2022
DOI: 10.3389/fcell.2021.816829
|View full text |Cite
|
Sign up to set email alerts
|

Rubicon in Metabolic Diseases and Ageing

Abstract: Autophagy is a conserved cellular degradation system that maintains intracellular homeostasis. Cytoplasmic components are engulfed into double-membrane vesicles called autophagosomes, which fuse with lysosomes, and resulting in the degradation of sequestered materials. Recently, a close association between autophagy and the pathogenesis of metabolic diseases and ageing has become apparent: autophagy is dysregulated during metabolic diseases and ageing; dysregulation of autophagy is intimately associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In autophagy, class III phosphatidylinositol-3-kinase (PI3KC3), which consists of three core components (Vps34, p150, Beclin-1), plays an important role in autophagosome biogenesis by catalyzing the formation of phosphatidylinositol-3-phosphate 47) . Rubicon directly binds with PI3KC3-related components and suppresses their function, resulting in inhibition of autophagosome-lysosome fusion processes 48) . However, overexpression of Rubicon leads to autophagy impairment in senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“…In autophagy, class III phosphatidylinositol-3-kinase (PI3KC3), which consists of three core components (Vps34, p150, Beclin-1), plays an important role in autophagosome biogenesis by catalyzing the formation of phosphatidylinositol-3-phosphate 47) . Rubicon directly binds with PI3KC3-related components and suppresses their function, resulting in inhibition of autophagosome-lysosome fusion processes 48) . However, overexpression of Rubicon leads to autophagy impairment in senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of Rubicon have been previously correlated with a reduction in autophagy activity in several cells, including neurons [ 28 ], cardiomyocytes [ 59 , 60 ], hepatocytes [ 61 ], adipocytes [ 62 , 63 ], and retinal epithelium [ 64 ]. Crescent Rubicon levels during aging have been associated with the decline in autophagy activity, arising as one of the potential target molecules in aging [ 28 , 29 , 65 ]. A recent study reported some components of this potential pathway [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, autosis is associated with reduced autophagic flux, blockade of autophagosome clearance and upregulation of Rubicon (RUN domain Beclin-1 interacting and cysteine-rich-containing protein) (11). Rubicon is one of the few endogenous inhibitors of autophagy during autophagosome maturation and autophagosome-lysosome fusion (12,13). Rubicon has been also involved in autophagy-independent functions including LAP (LC3-associated phagocytosis), endosomal trafficking and inflammatory responses (14-16).…”
Section: Introductionmentioning
confidence: 99%